The Effect of Lifestyle and Financial Literacy on Consumptive Behavior Millennials on Social Media Instagram - Jingga Arnesya, Novearhenada; Mulyono, Sugeng; Muawanah, Umi (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to test and analyze the influence of lifestyle and financial literacy on the consumptive behavior of the millennial generation on Instagram social media. The research approach used was an explanatory study with a population of 1,927 Instagram followers and a random sample of 331 people. The data were analyzed using multiple linear regression, F test, and t-test with a significance level of 5%. Previously, a classical assumption test was carried out. The results of the study show that partially, lifestyle and financial literacy have a significant effect on consumptive behavior. Simultaneously, lifestyle and financial literacy also have a significant effect on consumptive behavior, with financial literacy having a dominant influence. The implications of this study show the importance of controlling lifestyle and increasing financial literacy to reduce the consumptive behavior of the millennial generation. This research provides an in-depth understanding of the factors that influence consumptive behavior and can be used as a basis for designing more effective financial education strategies